Study Of Student Satisfaction And Acceptance In Batam City For Post-Pandemic Online Learning - Jefry Tan; El Vin Ho; Ivan Hendardi; Micheal Micheal; Jacky Jacky (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
During the pandemic, education institutions have applied online learning methods as emergency learning solutions during duress situations. Online learning affects the engagement,satisfaction, and perception of students. Because of that, to understand better how Perceived ease of use, Perceived usefulness, Satisfaction, and Acceptance intention affects students that participate in online learning during the pandemic, we conducted this research using an online survey (N = 390) among online learning students. We found that students are satisfied with online learning whenever the service is easy and more useful when used. We also identified every positive experience from online learning, therefore, encouraging enhancement. We also identified that every positive experience gained in online learning can increase the intention to use it again. This study will help students identify things that can increase student satisfaction and acceptance intentions during the post-Covid-19 pandemic.